AB0397 Pulmonary Hypertension in Rheumatoid Arthritis is Associated with Severe Left Ventricular Diastolic Dysfunction. (9th June 2015) - Sheth, T.; Broder, A.
Abstract : Background: Pulmonary hypertension (PHT) may contribute to the cardiovascular (CV) morbidity in rheumatoid arthritis (RA); however understanding of its etiology in RA remains limited. PHT may be under-recognized in RA and may be associated with factors other than interstitial lung disease (ILD) as conventionally thought. 1 Objectives: To estimate the frequency of PHT in adult RA (age >18) and to study associations of PHT with ILD, left ventricular diastolic dysfunction (LVDD), left ventricular systolic dysfunction (LVSD) and valvular heart diseases (VHD). Methods: We identified adult RA patients with at least one transthoracic echo (TTE) performed between 1997 and 2014. The RA patients were required to have at least two visits with recorded International Classification of Disease, Ninth Revision ( ICD9 code 714.0 and at least one prescription for a disease modifying anti-rheumatic drug. 2 PHT was defined as pulmonary artery systolic pressure (PASP) >35 mmHg on TTE. LVDD was defined as mild, moderate and severe as per established criteria based on mitral inflow velocities (MIV) (E and A) and lateral mitral annulus velocity (E') measured by Tissue Doppler Imaging (TDI). 3 LVSD was defined as LVEF <40%. Student's t test was used to compare continuous variables and chi-square test was used for categorical variables; p value of <0.05 was considered significant. Results: Total 187 patients satisfied inclusion criteria, of which 67 (35.8%) patients had PHT. Age, sex, race and ethnicity were not significantly different between patients with and without PHT (Table ). Patients with PHT had higher frequencies of coronary artery disease, peripheral arterial disease, and chronic kidney disease; although total comorbidities were not significantly different between the groups. Isolated LVDD was the most common association of PHT found in 22 (32.8%) of cases. Severe LVDD (E/A ≥1.5) was more prevalent in patients with PHT (22.3%) as compared to without PHT (6.7%). Other associations included LVSD in 10 (14.9%) cases, LVDD plus LVSD in 7 (10.4%) cases and aortic stenosis in 3 cases (4.5%). Eleven (16.41%) patients had ILD; of which 5 patients had ILD along with LVSD, LVDD or both. No differences in frequency of ILD were found between patients with and without PHT (12.5% v/s 16.4%). Conclusions: We found that PHT was present in over one third of RA patients who had a TEE performed at our center. CV comorbidities and LVDD were the most common associations. Severe LVDD was more frequent in patients with PHT. Although limited by its retrospective design and PHT definition by TTE, this is one of the largest studies to date looking at the frequency and the association between PHT and LVDD in RA. The strengths of the study include a well-defined study population and use of more accurate measures (MIV and TDI) to define LVDD. Enhanced recognition and early intervention of CV risk factors may prevent development and progression of PHT in RA patients. References: O'Dwyer DN, et al. Rheumatoid Arthritis associated interstitial lung disease. European Journal of Internal Medicine. Oct 2013;24(7):597-603. Kim SY, et al. Validation of rheumatoid arthritis diagnoses in health care utilization data. Arthritis Research & Therapy. 2011;13(1):R32. Redfield MM, et al. Burden of systolic and diastolic ventricular dysfunction in the community: appreciating the scope of the heart failure epidemic. JAMA: Jan 8 2003;289(2):194-202. Disclosure of Interest: None declared